Effect of fiber geometry and tenacity on the mechanical properties of fine aggregates concrete. (March 2016) - Halvaei, Mana; Jamshidi, Masoud; Latifi, Masoud
The effect of fiber cement interactions and its influence on flexural and tensile properties of cementitious composites are well known. In this research, acrylic fibers with different cross sectional and longitudinal shapes and different tensile strengths were selected as reinforcement of the specific fine aggregates concrete. Three point bending test, pullout test, and scanning electron microscopy were used to investigate flexural and pullout behavior of the composites. It was found that flexural toughness and pullout strength were increased 20% and 34%, respectively, by application of kidney shaped acrylic fibers in comparison to dog bone shaped acrylic fibers. It was also found that the flexural and pullout strength of composites containing non-crimped fibers are 33% and 26.5% higher than specimens with crimped fibers, respectively. Results showed that the flexural toughness and pullout strength of high tenacity fiber is 75% and 131% higher than regular fiber as well, respectively. The effect of fine aggregates on the adhesion of fibers to cement matrix was evaluated.